Anatoly Pavlovich Frumkin (1897-1962): сhief urologist of the Soviet Army and outstanding scientist - T. Sh. Morgoshiia (Вестник урологии, 2019)
The article marks the main years of the life and work of Professor A.P. Frumkin. It is shown that since 1926 for 36 years he worked in the hospital to them. S.P. Botkin (first as resident, and then head of the urology department). In 1939 he defended his doctoral thesis on the topic «Intravenous pyelography». From 1946 to 1962 He headed the Department of Urology at the CIU doctors. During the Great Patriotic War, he was the chief urologist of the Soviet Army. A.P. Frumkin is the author of over 150 scientific papers, including 4 monographs on various issues of urology. The fact that A.P. Frumkin was engaged in the development of methods for urethrography, intestinal plasty of the ureter and bladder (intestinal plasty), surgical treatment of urinogenital fistulas, treatment of purulent processes in the kidneys. It was noted that he introduced into practice a number of original urological operations: resection of the bladder neck in cancer, upper pyelolithotomy, subcapsular pyelotomy, bladder creation operation in extrastrophy, and others. A.P. Frumkin was the editor of the Urology department of the 2nd ed. BME, the deputy. editor of the Journal of Urology, editor of the Department of Urology of the Encyclopedic Dictionary of Military Medicine (1946), editor of the 13th volume of the Experience of soviet Medicine in the Great Patriotic War of 1941-1945. It is noted that since 1949, A. P. Frumkin was the permanent chairman of the All-Union and Moscow Urological Societies, an honorary member of the Royal Swedish Medical Society, the Society of Urologists of the German Democratic Republic and Poland. It is emphasized that the progressive development of the school created by A.P. Frumkin, and the dialectical continuation of his ideas in the works of his students, are the best monument to the creative activity of the scientist.